Picture Windows: Architecture of Privacy and Surveillance - Bärbel Harju (e-cadernos ces)
This essay, “Picture Windows: Architecture of Privacy and Surveillance,” explores how privacy became a public concern within the context of U.S. suburbanization during the 1950s. Suburban spaces and architecture represent changed notions of privacy, publicity, property and selfhood that correspond to broader ideological and historical transformations. Techniques, functions, and forms of privacy in American suburbs are examined against the background of prevalent fears and sensibilities during the early phase of the Cold War, in order to analyze how privacy is imagined, staged, negotiated, instrumentalized and made visible in the cultural, social, and political context of suburbanization.